Analysis of Stakeholder Engagement and Role in the Incentive Travel Destination Selection Process - Rudatin, Christina Lipuringtyas; Wardhani, Annisa (KnE Social Sciences, 2024)
Incentive travel tourists generally come in large groups and travel at the full expense of their company. Their expenditure is greater than ordinary tourists, but they receive less attention in Indonesia’s marketing strategy as quality tourists. This condition occurs due to a lack of understanding of the incentive travel business process. This lack of understanding is because research on the MICE industry is more concerned with meetings/conferences or exhibitions than incentive travel. Also, a reference book that discusses incentive travel and its relation to the choice of destination processes or destination marketing strategy is limited. This study aims to determine who is involved in the destination selection process and their relationships. The research method used is a qualitative method using desk research for data collection and content analysis for analytical methods. The research method used is a qualitative method using desk research for data collection and content analysis for the analysis method. Desk research was carried out by reviewing literature related to travel incentives and research report documents conducted by research institutions related to incentive travel. The result shows several parties’ engagement and role in the incentive travel destination selection process. Keywords: incentive travel, stakeholders, MICE industry, quality tourist, destination selection